The Burnout of Workers during Leisure Time Organization. Anykščiai Case (Laisvalaikio tyrimai, 2019)
Object of the analysis. The influence of employees’ burnout on organized leisure time.  Investigation problem. Previous studies have shown that burnout is a factor that affects civil servants. As the employees’ well-being can influence the organization’s activities, the impact of the burnout on employees is a topical issue and is increasingly being analysed among scientists, but the effect of the burnout in organizing leisure activities is not widely researched, therefore the problem of this work is relevant and explorable. The impact of the burnout on leisure time employment could be more effective in organizing activities. Research methods – scientific literature data analysis, statistical analysis of data, structured interview. Aim of the analysis: to evaluate the impact of the burnout of employees on organized leisure time. Goals of the analysis. 1. Based on the analysis of scientific literature, to reveal theoretical concepts of leisure-time organization and leisure services. 2. To introduce the burnout contact with leisure time organization. 3. To analyse the impact of staff burnout ton organized leisure time. The results of the research revealed that the determination of the manifestation of burnout is important, the status of the leisure organizer and the quality of the organized activity depend on it. Therefore, the burnout manifestations that have been observed in a timely manner must be stopped so that the leisure time is organized properly. It has been found that the causes of the burnout are related to the leisure organizer and leisure activities. It is important for leisure organizers to pay attention to the success of the organized activities. Many respondents identified burnout factors that prove burnout. Outcomes and conclusions. This confirms that the burnout negatively affects the quality of the leisure time. In order to improve leisure activities, it is suggested to take into account the recommendations: 1. To identify the illness and its manifestations, to identify the causes of the manifestation, to try to overcome them with their own help or with the help of specialists. 2. To create conditions for training and counselling for psychologists that would promote the resolution of stress situations, conflict management, overcoming stress and ensuring good working relationships in a leisure setting. 3. Organize seminars for leisure organizers in which there would be a possibility to improve. 4. Encourage leisure organizers to engage in activities that meet their personal needs and interests.Keywords: leisure organization, time planning, burnout.